Addressing food security, WASH and climate vulnerability: the WaterAid-CARE partnership in Timor-Leste - Alana George; Takara Morgan; J. Bhushan; M. Gamez (2014)
The small tropical country of Timor-Leste is in a period of social, political and environmental change. Its predominantly rural population is coping with aberrations in historical rainfall patterns and seasonal cycles, affecting communities’ ability to manage food and water security throughout the year. In 2012 CARE and WaterAid successfully applied for funding under the Australian Government’s Community Based Climate Change Action Grant. The objective of the joint project is to increase the adaptive capacity of women and men in vulnerable households living in Liquiça District with the goal of increasing resilience to the unavoidable impacts of climate change. The partnership has generated many interesting lessons, particularly around taking a catchment scale view and an integrated approach to managing water and food security. This paper will highlight selected lessons from the partnership, including addressing competing demands for water and mitigating conflict between its productive and domestic uses.